Voter responses to fiscal crisis: New evidence on preferences for fiscal adjustment in emerging markets - Martin Ardanaz; Evelyne Hübscher; Philip Keefer; Thomas Sattler (Inter-American Development Bank (IDB), 2024)
Though governments regularly implement fiscal adjustments to avert crisis, voter attitudes towards competing adjustment strategies are still poorly understood. A conjoint experiment with 8,000 survey respondents in Brazil, Colombia, Costa Rica, and Peru confirms that individuals prefer spending- to tax-based adjustments in general. However, preferences change dramatically depending on which specific tax and spending adjustments are included and on individuals' personal characteristics. Consistent with their broad preferences for spending- over tax-based adjustments, respondents oppose increases in the personal income tax and support public employment cuts. However, they support or are indifferent towards higher corporate income or value-added taxes and they oppose cuts in social assistance. Preferences for fiscal adjustment also depend on voter characteristics that are unrelated to their pecuniary interests. Ideology, social beliefs, and trust in government significantly influence their preferences for tax- or spending-based adjustments in general and for the specific composition of those adjustments.
Keywords: D72; E62; H62; 330; fiscal adjustment; taxes; public expenditures; conjoint experiment